Law No. 219 of the year 2017 Amending Certain Provisions of the Inheritance Law No. 77 of the Year 1943 = قانون رقم 219 لسنة 2017 بتعديل بعض أحكام القانون رقم 77 لسنة 1943 بشأن المواريث - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic